Вплив показників робочої сили на якість ремонту машин - Дашивець, Галина Іванівна; В’юник, Ольга Володимирівна; Dashyvets Halyna; Viunyk Olha (Запоріжжя : ТДАТУ, Видавничій дім "Гельветика", 2025)
UA: Основною метою роботи було виявлення і дослідження комплексних та одиничних показників рівня робочої сили сервісного підприємства, які впливають на якість ремонту машин. На рівень робочої сили впливають кваліфікація робітників, їхнє ставлення до роботи, дисципліна праці і технології. Виконано ранжування всіх показників; за результатами експертної оцінки встановлено вагомість комплексних і одиничних факторів виробничих ресурсів; побудовано діаграми коефіцієнтів вагомості для показників. Серед показників кваліфікації найбільш вагомим виявився показник рівня знання технології; серед показників ставлення до роботи – показник якості робіт; серед показників дисципліни праці та технології – показник технологічної дисципліни. Розглянуті чинники дали змогу сформулювати основні напрями підвищення якості праці виконавців, що призведе до підвищення якості ремонту машин. /// EN: The quality of machine repair is influenced by the level of production resources, which consist of the following factors: availability and quality of the technological base, coverage and quality of engineering training of production, level of labor force. Identification and research of complex and single indicators of the first two factors was carried out in previous works. This work is devoted to determining the labor force indicators that affect the quality of machine repair. The quality of work at service enterprises may be low due to non-compliance with technological and labor discipline, failure to ensure the accurate execution of the production process; unsystematic increase in the level of technical training of personnel; failure to apply advanced forms of remuneration, material and moral incentives for performers. The level of the workforce is influenced by factors: the qualifications of workers, their attitude to work, labor discipline and technology are complex indicators. In turn, they consist of individual indicators. Thus, for the indicator of the qualifications of the workforce, these are the category of workers, length of service, education, level of knowledge of technology; for the indicator of the attitude of workers to work - compliance with standards, quality of work, condition of the tool, individual labor productivity, maintenance of the workplace in order; for the indicator of the labor discipline of workers and technology – use of working time, development of skills and professional growth, diligence (fulfillment of orders), technological discipline. A working group of experts developed a questionnaire to assess the impact of factors on the quality of services. Five levels of possible values of single indicators were introduced. The indicators were ranked, and diagrams of weighting coefficients for single factors of the workforce were constructed based on the results of the expert assessment. Among the indicators of qualification, the most significant indicator was the level of knowledge of technology; among the indicators of attitude to work, the indicator of quality of work; among the indicators of labor discipline and technology, the indicator of technological discipline. The factors considered allowed us to formulate the main directions for improving the quality of work of performers, which in turn will lead to an improvement in the quality of machine repairs.
The influence of labor force indicators on the quality of machine repair
Keywords: якість ремонту машин; робоча сила; експертна оцінка; діаграма; кваліфікація робітника; quality of machine repair; labor; expert assessment; diagram; worker qualification